Quantitative Skills Training for SNBT Preparation at SMA Negeri 2 Parepare South Sulawesi - Miftahulkhairah, Miftahulkhairah; Rahmi, Nur; Ekasasmita, Wahyuni; S, Ahmad Fajri; Adhalia H, Nurul Fuady (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This service activity aims to improve students' quantitative abilities, especially in the SNBT test. The method of implementing this service used training, test simulations and discussions, as well as tips and strategies for solving quantitative ability questions. Assessment tools used during the activity included a pretest, posttest, and questionnaire. The analytical technique to assess the activity's success involved comparing the outcomes of the pre-test and post-test administered. The Results showed that there was an average increase in the scores of the participants' Quantitative Skills test. Overall, the average percentage increase in the participants' Quantitative Skills test scores was 13% from the pre-test scores. It can be concluded that the quantitative skills training provided positively enhanced the student's knowledge and skills, particularly in solving scholastic problems related to the Quantitative Skills test for the upcoming SNBT. Based on the survey, 53.1% of participants were highly satisfied with the conducted training activities and agree that such activities should be continued.